Incorrect thinking process prediction for negative numbers subtraction operation involving positive with negative integers - Elango Periasamy, (Pusat Perkembangan Pelajar, UKM, 2014)

(untitled)
This study was divided into two parts. The first part was to identify the incorrect answer produced by the respondents for each item and its frequency. Then, the second part was to predict the incorrect thinking process with respect to its frequencies that respondent might have adapted in solving such sentence questions incorrectly. The respondents of this study were five mathematics teachers and 124 students aged 14 years old from Malaysian secondary school. The finding shows types of mistakes made by the students for each type of items tested and the prediction of incorrect thinking process respectively. This paper focused on the third category: subtraction operation involving positive with negative integers. The findings revealed that in depth analysis into the students thinking process is an essential knowledge for teachers to re-assess their teaching and correct students their misconceptions.